An Efficient Ligandless Palladium-catalyzed Protocol for Suzuki-Miyaura Coupling Reaction of Potassium Aryltrifluoroborates in Water - Liu, Leifang; Liu, Mingcheng; Yang, Jianhua; Zhu, Baoyong; Wang, Xinfang (Current Organic Chemistry, 2018)
An efficient and ligandless catalytic system was developed for the Suzuki- Miyaura coupling reactions of potassium aryltrifluoroborates in pure water. Using TEAB as additives, Pd(OAc)2 was found to be very efficient for the Suzuki-Miyaura coupling of potassium aryltrifluoroborates with various aryl and heteroaryl bromides in pure water with Na2CO3 as a base, affording the desired products in moderate to excellent yields.
Keywords: aryl bromide